SIRT3/6/7: promising therapeutic targets for pulmonary fibrosis - Huang, Pingping; Qin, Dan; Qin, Yanling; Tao, Sha; Liu, Guangnan (Frontiers in Cell and Developmental Biology, 2025)
Pulmonary fibrosis is a chronic progressive fibrosing interstitial lung disease of unknown cause, characterized by excessive deposition of extracellular matrix, leading to irreversible decline in lung function and ultimately death due to respiratory failure and multiple complications. The Sirtuin family is a group of nicotinamide adenine dinucleotide (NAD+) -dependent histone deacetylases, including SIRT1 to SIRT7. They are involved in various biological processes such as protein synthesis, metabolism, cell stress, inflammation, aging and fibrosis through deacetylation. This article reviews the complex molecular mechanisms of the poorly studied SIRT3, SIRT6, and SIRT7 subtypes in lung fibrosis and the latest research progress in targeting them to treat lung fibrosis.